First nosocomial infections in children supported by veno-arterial extracorporeal membrane oxygenation (VA-ECMO) - Vladimir L. Cousin; Robert Rodriguez-Vigouroux; Oliver Karam; Peter Rimensberger; Klara M. Posfay-Barbe (BMC, 2023)
Abstract Background Veno-arterial Extracorporeal Membrane Oxygenation (VA-ECMO) is a standard procedure for patient with refractory shock in Pediatric Intensive Care Unit (PICU). There is a paucity of data on the time relationship between VA-ECMO support, nosocomial infection occurrence, and PICU length of stay (LOS). The aim of this study was to determine the characteristics and impact of ECMO-related infections. Methods This is a retrospective study from 01/2008 to 12/2014, enrolling children with a VA-ECMO support for > 6 h. We recorded the first PICU infection during the VA-ECMO run, defined as a positive microbiological sample with clinical signs of infection or clinical signs of severe infection without positive sample. Results During the study period, 41 patients (25/41 male) were included, with a median age of 41.2 months (IQR 12.9-89.9) and a 53% mortality rate. Median time on VA-ECMO was 4.2 d (IQR 2-7.1), median PICU LOS was 14.7 d (IQR 4,7-26,9). Overall, 34% patients developed an infection, with an incidence of 60/1000 VA-ECMO days. Median time to first infection was 4 d (IQR 3-5), with Pseudomonas spp. being the most commonly detected microorganism (42%). Infected sites were ventilator-associated pneumonia (9/14), sternotomy infection (2/14), bloodstream (2/14) and urinary tract infections (1/14). Longer VA-ECMO support (> 5 d) (OR 5.9 (CI 95% 1.4-24.6; p = 0.01) and longer PICU stay (> 14 d) (OR 12 (95% CI 2.2-65.5; p = 0.004) were associated with infection. Conclusion In this single-center study, we underlined the high proportion and early occurrence of infections in patient on VA-ECMO, mostly in the first week. As infection was an early event, it may prolong the duration of VA-ECMO support and PICU LOS. Further research is needed to better understand the impact of infections on VA-ECMO and develop prevention strategies.